Band gap measurement of SrFeO3−δ by ultraviolet photoelectron spectroscopy and photovoltage method - Huang, H. (2013)
There are very important characteristics of partial substitution of the cations at both A and B sites in ABO3 perovskite structure. In this report, SrFeO(3−δ) (SFO) photocatalyst powder was synthesized by a high temperature solid state reaction method. The morphology and crystalline structure of the obtained samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscopy (TEM). The XRD, TEM and SAED patterns indicated that a single cubic perovskite phase of SrFeO(3−δ) (SFO) oxide has been successfully synthesized. The surface composition of the SrFeO(3−δ) sample was characterized by X-ray photoelectron spectroscopy (XPS). The XPS results showed that the iron existing in the SrFeO(3−δ) perovskite structure is composed of a mixture of Fe3+ and Fe4+. Due to the high absorbance of the SrFeO(3−δ) powder, the Kubelka–Munk model and UV–visible measurement were not applicable. Therefore, in order to study the band positions further, the valence band edges for electronic band gaps were obtained for SrFeO(3−δ) by ultraviolet photoelectron spectroscopy (UPS) while the conduction band position was obtained by photovoltage method.